Analysis of Transformational Leadership and Organizational Justice on Organizational Commitment With Job Satisfaction as a Mediating Variable at the National Narcotics Agency North Sumatra Province - Henri Liranto Petrus. S; Elfitra Desy Surya; Sri Rahayu (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Organizational commitment is a key factor in supporting the success of the North Sumatra Provincial National Narcotics Agency (BNNP Sumut) in preventing, eradicating, and rehabilitating drug abuse. High work demands, task risks, and organizational pressures require effective leadership and fair organizational treatment so that employees remain satisfied and highly committed. This study aims to analyze the influence of transformational leadership and organizational justice on organizational commitment with job satisfaction as a mediating variable at BNNP North Sumatra. This study uses a quantitative approach with a survey method. The population and sample of this study were all 84 employees of BNNP North Sumatra. Data collection was conducted through questionnaires, while data analysis used the Partial Least Squares (PLS) method with the help of the SmartPLS application. The results showed that transformational leadership and organizational justice had a positive and significant effect on job satisfaction and organizational commitment. Job satisfaction also had a positive and significant effect on organizational commitment. In addition, job satisfaction was found to mediate the influence of transformational leadership and organizational justice on organizational commitment. These findings indicate that increasing the organizational commitment of BNNP Sumut employees can be achieved through the implementation of inspirational transformational leadership and consistent and transparent organizational justice, with employee job satisfaction as a mediating factor. This study is expected to serve as a practical reference for BNNP Sumut leaders in formulating human resource management policies oriented toward strengthening organizational commitment.